The why and how of sunken stomata: does the behaviour of encrypted stomata and the leaf cuticle matter? - Šantrůček, Jiří (Annals of botany, 2022)
BACKGROUND: Stomatal pores in many species are separated from the atmosphere by different anatomical obstacles produced by leaf epidermal cells, especially by sunken stomatal crypts, stomatal antechambers and/or hairs (trichomes). The evolutionary driving forces leading to sunken or 'hidden' stomata whose antechambers are filled with hairs or waxy plugs are not fully understood. The available hypothetical explanations are based mainly on mathematical modelling of water and CO2 diffusion through superficial vs. sunken stomata, and studies of comparative autecology. A better understanding of this phenomenon may result from examining the interactions between the leaf cuticle and stomata and from functional comparisons of sunken vs. superficially positioned stomata, especially when transpiration is low, for example at night or during severe drought. SCOPE: I review recent ideas as to why stomata are hidden and test experimentally whether hidden stomata may behave differently from those not covered by epidermal structures and so are coupled more closely to the atmosphere. I also quantify the contribution of stomatal vs. cuticular transpiration at night using four species with sunken stomata and three species with superficial stomata. CONCLUSIONS: Partitioning of leaf conductance in darkness (gtw) into stomatal and cuticular contributions revealed that stomatal conductance dominated gtw across all seven investigated species with antechambers with different degrees of prominence. Hidden stomata contributed, on average, less to gtw (approx. 70 %) than superficial stomata (approx. 80 %) and reduced their contribution dramatically with increasing gtw. In contrast, species with superficial stomata kept their proportion in gtw invariant across a broad range of gtw. Mechanisms behind the specific behaviour of hidden stomata and the multipurpose origin of sunken stomata are discussed.
Keywords: leaf; Olea europaea; epidermis; Capsicum annuum; Droughts; listy rostlin; Plant Transpiration; stomatal transpiration; období sucha; průduchy rostlin; Clusia rosea; Plant Leaves; Sunken stomata; cuticular transpiration; stomatal encryptation; Carbon Dioxide; stomatal antechamber; Ficus elastica; voda; Water; Brassica oleracea; oxid uhličitý; Arabidopsis thaliana; Plant Stomata; nocturnal transpiration; transpirace rostlin; Nerium oleander; trichomes